A Recent Research on Malware Detection Using Machine Learning Algorithm: Current Challenges and Future Works - Gorment N.Z.; Selamat A.; Krejcar O. (Springer Science and Business Media Deutschland GmbH, 2023)
Barium compounds; Cybersecurity; Data mining; Decision trees; Evolutionary algorithms; K-means clustering; Learning algorithms; Malware; Network security; Sodium compounds; Support vector machines; 'current; Comparatives studies; Cyber security; K-means; Machine learning algorithms; Malware attacks; Malware detection; Metaheuristic; Recent researches; Systematic literature review; Nearest neighbor search